Prevalence of porcine circoviruses (PCV2 and PCV3) in slaughtered pigs with different pleurisy lesions score: Coinfections with Mycoplasma hyopneumoniae, Actinobacillus pleuropneumoniae, and Pasteurella multocida - Braga, Eduarda Ribeiro [UNESP]; Panneitz, Ana Karolina [UNESP]; Petri, Fernando Antônio Moreira [UNESP]; de Oliveira, Luís Guilherme [UNESP] (Elsevier, 2025)
Circovirus porcine (PCV) is a widespread pathogen in swine, consisting of four species: PCV1, PCV2, PCV3, and PCV4. Coinfection with other pathogens exacerbates the severity of Porcine Respiratory Disease Complex (PRDC), leading to significant economic losses. In Brazil, pleurisy lesions in pigs, often due to chronic inflammation from bacterial, viral, and environmental factors, are a major economic concern. This study aimed to detect PCV2 and PCV3 in PRDC by identifying these viruses in lung and pleural samples from pigs with varying degrees of pleurisy lesions. A total of 130 lung and pleural samples were collected from a slaughterhouse and analyzed using the Slaughterhouse Pleurisy Evaluation System (SPES). The qPCR results showed that 63.9 % of lung samples tested positive for PCV2, while 29.2 % were positive for PCV3. In pleural samples, 30.7 % were positive for PCV2 and 37.7 % for PCV3. Additionally, other pathogens, including Mycoplasma hyopneumoniae (Mhyo), Actinobacillus pleuropneumoniae (APP), and Pasteurella multocida (PM), were also detected in both lung and pleural samples. Coinfections were frequently observed in both tissues. Sequencing revealed that the PCV2d variant was the most prevalent; however, we also identified positive samples for PCV2c, a rare finding in Brazil. Our study highlights the complex interactions in PRDC, as well as the presence of PCV2 and PCV3 in this context.